Effects of psychosocial function in pediatric-onset inflammatory bowel disease during the coronavirus disease 2019 pandemic - Zhang, Huihui; Yang, Yun; Zhao, Xixi; Hu, Huajian; Liu, Jia; Zhan, Xue; Song, Xiaomei; Guo, Hong; Li, Zhongyue; Zhou, Xiaoqin (Frontiers in Pediatrics, 2023)
Background and Aims Research on the effect of the coronavirus disease 2019 (COVID-19) pandemic on psychosocial function in patients with pediatric-onset inflammatory bowel disease (PIBD) is limited. This study aimed to evaluate the psychological status of patients with PIBD before and during the pandemic, and the relationship between mental health and disease activity. Methods This study was a retrospective cohort study. Statistical analyses were performed to assess the relationship between demographic, clinical data and psychological data (questionnaires) of PIBD patients before and during the epidemic. The anxiety and depression emotional status of the guardians during the pandemic were evaluated. Results In the PIBD follow-up cohort, 42 patients(male 61.9%) were included. Female with PIBD had lower pediatric quality of life inventory(PedsQL) scores (P = 0.007) and higher spence children's anxiety scale(SCAS) scores (P = 0.038) than male. The pandemic did not have a substantial impact on PedsQL, pittsburgh sleep quality index(PSQI), SCAS, or children's depression inventory(CDI) in patients with PIBD. The self-rating anxiety scale(SAS) score, anxiety rate, self-rating depression scale(SDS) score, and depression rate of PIBD guardians were significantly higher than those of healthy controls (SAS, P = 0.008; SDS, P = 0.001). Conclusions Female children with PIBD were more vulnerable to decreased QOL and increased anxiety than male children. The anxiety and depression status of PIBD guardians were significantly higher than those of healthy controls during the COVID-19 pandemic. But the COVID-19 pandemic did not significantly affect quality of life(QOL), sleep, anxiety, or depressive mood of patients with PIBD in our study.